WASP-147b, 160Bb, 164b, and 165b: two hot Saturns and two Jupiters, including two planets with metal-rich hosts. Issue 1 (3rd October 2018) - Lendl, M; Anderson, D R; Bonfanti, A; Bouchy, F; Burdanov, A; Cameron, A Collier; Delrez, L; Gillon, M; Hellier, C; Jehin, E; Maxted, P F L; Nielsen, L Dyregaard; et al.
Abstract: We report the discovery of four transiting hot Jupiters, WASP-147, WASP-160B, WASP-164, and WASP-165 from the WASP survey. WASP-147b is a near Saturn-mass ( MP = 0.28 MJ ) object with a radius of$1.11 \, {R_{J}}$ orbiting a G4 star with a period of 4.6 d. WASP-160Bb has a mass and radius ($M_p = 0.28 \, {M_{J}}$, $R_p = 1.09 \, {R_{J}}$ ) near-identical to WASP-147b, but is less irradiated, orbiting a metal-rich ([Fe/H]* = 0.27) K0 star with a period of 3.8 d. WASP-160B is part of a near equal-mass visual binary with an on-sky separation of 28.5 arcsec. WASP-164b is a more massive ($M_P = 2.13 \, {M_{J}}$, $R_p = 1.13 \, {R_{J}}$ ) hot Jupiter, orbiting a G2 star on a close-in ( P = 1.8 d), but tidally stable orbit. WASP-165b is a classical ($M_p = 0.66 \, {M_{J}}$, $R_P = 1.26 \, {R_{J}}$ ) hot Jupiter in a 3.5 d period orbit around a metal-rich ([Fe/H]* = 0.33) star. WASP-147b and WASP-160Bb are promising targets for atmospheric characterization through transmission spectroscopy, while WASP-164b presents a good target for emission spectroscopy.